2018
DOI: 10.1111/cp.12104
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of the biosocial model to borderline traits

Abstract: Background A number of theories have been proposed to account for the development of borderline personality disorder (BPD). The biosocial model considers emotional dysregulation to be central to the disorder, caused in turn by an emotionally vulnerable child being raised in an invalidating environment. This aetiological model is potentially too broad, as many of these constructs may be equally important to other mental health conditions, making the model non‐specific to BPD. Method We sought to contrast the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…In fact, parental invalidation was associated with other psychological variables not predicted by Biosocial Therory. For example Gill, Warburton, and Beath (2018) showed that parental invalidation was related to chronic worry, and Arnett, Roach, Elzy, and Jelsone-Swain ( 2019) founded an association with empathy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, parental invalidation was associated with other psychological variables not predicted by Biosocial Therory. For example Gill, Warburton, and Beath (2018) showed that parental invalidation was related to chronic worry, and Arnett, Roach, Elzy, and Jelsone-Swain ( 2019) founded an association with empathy.…”
Section: Discussionmentioning
confidence: 99%
“…All studies were cross-sectional, with the exception of the one by Crystal (2017), which adopted a longitudinal design. Only two studies (Gill et al, 2018; Keng et al, 2019) used clinical samples, whereas all other studies recruited college or community participants. Specifically, Gill and colleagues (2018) recruited individuals with BPD traits who were currently engaged in therapy, whereas Keng and colleagues (2019) recruited psychiatric patients in a hospital setting…”
Section: Methodsmentioning
confidence: 99%
“…The DERS has good test–retest reliability (ρ I = .88, p < . 01), internal consistency (α = .93–.94), and predictive validity of psychopathology in which emotional dysregulation plays a role (Gill, Warburton, & Beath, 2018; Gratz & Roemer, 2004, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Emotion regulation difficulties are associated with many clinical disorders, including borderline personality disorder (Gill & Warburton, 2014; Gill, Warburton, & Sweller, 2018; Salsman & Linehan, 2012; Sturrock & Mellor, 2014), eating disorders (Svaldi, Griepenstroh, Tuschen‐Caffier, & Ehring, 2012), anxiety disorders (Mennin, McLaughlin, & Flanagan, 2009), depression (Nickerson et al., 2015), and post‐traumatic stress disorder (Ehring & Quack, 2010; Nickerson et al., 2015). Perhaps the most widely used measure of the construct is the Difficulties in Emotion Regulation Scale (DERS; Gratz & Roemer, 2004), a six‐factor self‐report measure of the construct.…”
Section: Introductionmentioning
confidence: 99%